1993
DOI: 10.1128/aem.59.7.2150-2160.1993
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Typical Marine Bacteria by Dilution Culture: Growth, Maintenance, and Characteristics of Isolates under Laboratory Conditions

Abstract: Marine bacteria in Resurrection Bay near Seward, Alaska, and in the central North Sea off the Dutch coast were cultured in filtered autoclaved seawater following dilution to extinction. The populations present before dilution varied from 0.11 x 109 to 1.07 x 109 cells per liter. The mean cell volume varied between 0.042 and 0.074 ,um3, and the mean apparent DNA content of the cells ranged from 2.5 to 4.7 fg of DNA per cell. All three parameters were determined by high-resolution flow cytometry. All 37 strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
1
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(162 citation statements)
references
References 82 publications
2
151
1
8
Order By: Relevance
“…Sphingopyxis alaskensis is a marine bacterium that was isolated as a numerically abundant species from permanently cold (4-10°C) waters in the Alaskan and Japanese North Pacific, and the North Sea (Schut et al, 1993;1997;Eguchi et al, 1996;2001). Its ability to proliferate to high numbers illustrates its capacity to compete effectively at low temperature, and under all the other biotic and abiotic factors prevailing at the times of sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Sphingopyxis alaskensis is a marine bacterium that was isolated as a numerically abundant species from permanently cold (4-10°C) waters in the Alaskan and Japanese North Pacific, and the North Sea (Schut et al, 1993;1997;Eguchi et al, 1996;2001). Its ability to proliferate to high numbers illustrates its capacity to compete effectively at low temperature, and under all the other biotic and abiotic factors prevailing at the times of sampling.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that most of the bacterial species are nonplatable because they are adapted to low nutrient concentrations and reach only low maximum growth rates (K-selected) [2,10]. The physiology and ecological role of these unknown bacterial species in most cases can only be assessed after their isolation in pure culture.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters were then used to systematically improve culturability. In addition, we established de¢ned growth media to replace the often used complex media (e.g., R2A [23]), or autoclaved sitewater [2,19].…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment of microbial communities that couple anaerobic acetate oxidation to Mn 31 reduction Enrichment cultures were initiated by transferring 2.5 g of homogenized sediment from the Mn 21 -rich redox zone (30-50 mm depth interval) to 100 mL of anaerobic growth medium in serum bottles under a N 2 atmosphere. Growth medium consisted of sterile sulphate-free artificial seawater (Schut et al, 1993) diluted two-fold with anoxic deionized water to mimic salt marsh ionic strength. Replicate enrichments were amended with either 100 mM, 1 mM, or 14 mM sodium sulphate.…”
Section: Sediment Sampling and Field Measurementsmentioning
confidence: 99%